2008
DOI: 10.1021/es072029+
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Aircraft Engine Emissions Characterization of in-Use Aircraft at Hartsfield-Jackson Atlanta International Airport

Abstract: The emissions from in-use commercial aircraft engines have been analyzed for selected gas-phase species and particulate characteristics using continuous extractive sampling 1-2 min downwind from operational taxi-and runways at HartsfieldJackson Atlanta International Airport. Using the aircraft tail numbers, 376 plumes were associated with specific engine models. In general, for takeoff plumes, the measured NO x emission index is lower (∼18%) than that predicted by engine certification data corrected for ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 33 publications
(45 reference statements)
9
84
1
Order By: Relevance
“…Several studies report that particles in the nucleation range are emitted from aircraft engines (e.g. Anderson et al, 2005;Herndon et al, 2008;Kinsey et al, 2010;Mazaheri et al, 2009Mazaheri et al, , 2013Masiol and Harrison, 2014;Lobo et al, 2015Lobo et al, , 2012 as well as from other anthropogenic (e.g. Schneider et al, 2005;Chen et al, 2011;Cheung et al, 2012;Stevens et al, 2012;Kumar et al, 2013Kumar et al, , 2014Vu et al, 2015b) and natural (e.g.…”
Section: Warm Seasonmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report that particles in the nucleation range are emitted from aircraft engines (e.g. Anderson et al, 2005;Herndon et al, 2008;Kinsey et al, 2010;Mazaheri et al, 2009Mazaheri et al, , 2013Masiol and Harrison, 2014;Lobo et al, 2015Lobo et al, , 2012 as well as from other anthropogenic (e.g. Schneider et al, 2005;Chen et al, 2011;Cheung et al, 2012;Stevens et al, 2012;Kumar et al, 2013Kumar et al, , 2014Vu et al, 2015b) and natural (e.g.…”
Section: Warm Seasonmentioning
confidence: 99%
“…Herndon et al, 2008;Masiol and Harrison, 2014 and references therein) but also arise from other combustion sources. For example, Carslaw et al (2006) estimated that airport operations in 2001/4 accounted for ∼ 27 % of the annual mean NO x and NO 2 at the airfield boundary and less than 15 % (< 10 µg m −3 ) at background locations 2-3 km downwind of the airport.…”
Section: Introductionmentioning
confidence: 99%
“…Although this sector accounts for a relatively small fraction of the global CO 2 emissions from fossil fuels (2.6 % in the year 2004; Lee et al, 2010), it has a substantial impact on climate due to a wide range of non-CO 2 effects, including ozone formation and methane destruction via NO x emissions, direct and indirect aerosol effects from sulfate and black carbon (BC), the formation of contrail and contrailcirrus clouds, and the perturbation of natural cirrus clouds due to BC (see Sausen et al, 2005;Lee et al, 2010, and references therein). In addition to impacts on the climate, emissions of particulate matter from aircraft and related activities at and in the vicinity of airports can have detrimental effects on air quality and related impacts on human health (Herndon et al, 2004(Herndon et al, , 2008Schürmann et al, 2007). The study by Barrett et al (2010) also found significant impacts on air quality from aircraft emissions at cruise level, but the resulting health impacts have been questioned by H. Lee et al (2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a strong relationship between emissions during the landing and takeoff (LTO) cycle below 1000 m altitude and air quality near 5506 H. Lee et al: Impacts of aircraft emissions on the air quality near the ground airports (Herndon et al, 2004;Schurmann et al, 2007;Herndon et al, 2008). Tarrason et al (2004) found that the emission by aircraft during climb/descent and during cruise, the so called non-LTO emissions occurring above 1 km in altitude, can have a larger impact than LTO emissions on air quality in Europe because of the relatively large amount of non-LTO emissions compared to LTO emissions.…”
Section: Introductionmentioning
confidence: 99%